Education: the practice of freedom. Vert. Introd. by D. Goulet (Writers and Readers Publishing Cooperative, 1976)
Contains: Paulo Freire, Education as the practice of freedom. Original title: Educaçáo como prática da liberdade. 1967. and Paulo Freire, Extension or communication. Pref. by J. Chonchol. Original title: Extensión y comunicacion. 1969. This book first publ. under the title: Education for critical conscousness. 1974.